2021
DOI: 10.3329/jemc.v10i2.53536
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung’s Disease: Diagnosis and Management

Abstract: Hirschsprung’s disease (HD) is a rare genetic congenital defect of intestine causing failure of migration of parasympathetic ganglionic cells in some definite part of intestine, resulting in functional intestinal obstruction. It commonly involves rectosigmoid region of colon but other parts of colon or total colon, even small intestine may be affected. Incidence is 1/5000 live births. It is one of the common pediatric surgical problems and 2nd most organic cause of constipation. Symptoms may be evident from 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Delayed passage of meconium, Abdominal distension, Constipation, Vomiting, failure to pass and fever are common symptoms in HD patients Table 2 shows the symptoms for HD and non-HD cases. The delayed passage of meconium is the most common symptom of HD in our study which was almost the same result mentioned by [15] as the delayed passage of meconium in HD patients was reported to be about 90 % of patients in the HD group. While in [16] study reported the delayed passage of meconium in HD patients was to be about 81 %.…”
Section: Clinical Features: Symptomssupporting
confidence: 90%
“…Delayed passage of meconium, Abdominal distension, Constipation, Vomiting, failure to pass and fever are common symptoms in HD patients Table 2 shows the symptoms for HD and non-HD cases. The delayed passage of meconium is the most common symptom of HD in our study which was almost the same result mentioned by [15] as the delayed passage of meconium in HD patients was reported to be about 90 % of patients in the HD group. While in [16] study reported the delayed passage of meconium in HD patients was to be about 81 %.…”
Section: Clinical Features: Symptomssupporting
confidence: 90%